The Umbul Dance in Situraja in the Trajectory of History and Local Cultural Education - Ajid Thohir; Syahidah Qolbiya Sakinah; Mohamad Aqbil Wikarya Abdul Karim; Muhamad Zaky Avicena; Johan Setiawan (Gawi: Journal of Action Research, 2026)
The Umbul Dance is a traditional performing art form that emerged from the helaran tradition of the agrarian community in Situraja, Sumedang Regency, West Java. This dance has spiritual, aesthetic, and pedagogical dimensions, and has become a cultural symbol of the Sundanese people, passed down orally across generations. This study aims to examine the origins, transformation of form and function, and the role of the Umbul Dance in local cultural education. Using the primary theoretical foundation of Louis Gottschalk, who emphasizes reconstructing the significance of the past through a process of critical selection, verification, and interpretation of sources, using a cultural history approach, oral history according to Paul Thompson and Alessandro Portelli, and ethnopedagogy based on Lev Vygotsky's sociocultural theory, this study employed in-depth interviews, participant observation, and visual documentation. The findings indicate that the Umbul Dance has undergone significant revitalization since 1976 through the active participation of community leaders and the arts community, successfully transforming it from a local ritual into a representative art form in education. Its existence is integrated into the Independent Curriculum as part of the Pancasila Student Profile Strengthening Project (P5) to instill local character values. This research confirms that the Umbul Dance is not merely a cultural heritage, but also a contextual educational strategy instrument based on local wisdom that can respond to the challenges of the times.